[PP.05.18] POSTPRANDIAL LEVELS OF BRANCH CHAINED AND AROMATIC AMINO ACIDS ASSOCIATED WITH FASTING GLYCAEMIA. (September 2016) - Ottosson, F.; Ericson, U.; Almgren, P.; Nilsson, J.; Magnusson, M.; Fernandez, C.; Melander, O.
Abstract : Objective: High overnight fasting plasma concentrations of the three amino acids isoleucine, phenylalanine and tyrosine have been associated with increased risk of insulin resistance and incidence of type 2 diabetes. It is unknown whether these associations are diet or metabolism driven. We examined how the dietary protein source affects the postprandial circulating profile of the three diabetes associated amino acids (DMAAs) and tested whether the postprandial DMAAs profiles are associated with fasting glycaemia. Design and method: We used a cross-over design, with twenty-one healthy individuals and 4 different isocaloric test meals containing proteins from different dietary sources (dairy, fish, meat and plant foods). Analysis of the postprandial DMAAs concentrations was performed using targeted mass spectrometry. A DMAA score was defined as the sum of all three amino acid concentrations. Results: The postprandial area under the curve (AUC) of all three amino acids and the DMAA score were significantly greater after intake of the meal with dairy protein compared to intake of the three other meals. Whereas fasting concentrations of the DMAA score and phenylalanine weakly associated with glucose concentration in the fasted state, the postprandial AUC for the DMAA score and all three amino acids strongly associated with fasting glucose level. Conclusions: Dairy protein intake has the most potent effect on DMAAs postprandial profile. Stronger associations between levels of DMAAs and fasting glucose were found in the postprandial state than in the overnight fasted state. This indicates the importance of the postprandial kinetics and metabolism of DMAAs in understanding the overall association between DMAAs and fasting glycaemia.